2015
DOI: 10.1073/pnas.1502052112
|View full text |Cite
|
Sign up to set email alerts
|

Randomization and resilience of brain functional networks as systems-level endophenotypes of schizophrenia

Abstract: Schizophrenia is increasingly conceived as a disorder of brain network organization or dysconnectivity syndrome. Functional MRI (fMRI) networks in schizophrenia have been characterized by abnormally random topology. We tested the hypothesis that network randomization is an endophenotype of schizophrenia and therefore evident also in nonpsychotic relatives of patients. Head movement-corrected, resting-state fMRI data were acquired from 25 patients with schizophrenia, 25 first-degree relatives of patients, and 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
91
2
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 122 publications
(103 citation statements)
references
References 58 publications
(63 reference statements)
8
91
2
1
Order By: Relevance
“…A recent graph theoretical network study of patients with schizophrenia and first‐degree relatives of patients did reveal a reduced clustering coefficient in both groups with respect to controls (Lo et al. 2015). In comparison with this study, a smaller sample size ( n  = 79) was used, as well as absolute wavelet correlation matrices to construct binary undirected graphs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent graph theoretical network study of patients with schizophrenia and first‐degree relatives of patients did reveal a reduced clustering coefficient in both groups with respect to controls (Lo et al. 2015). In comparison with this study, a smaller sample size ( n  = 79) was used, as well as absolute wavelet correlation matrices to construct binary undirected graphs.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, a graph theoretical network study of patients with schizophrenia and first‐degree relatives of patients has shown similar functional network randomization between these two groups, suggesting that this represents a marker of familial risk (Lo et al. 2015). The thus far more frequently used traditional methods (seed‐based correlation, ICA) consistently showed that unaffected siblings/first‐degree relatives share functional connectivity network alterations with their affected siblings (e.g., Whitfield‐Gabrieli and Ford 2012; Fornito et al.…”
Section: Introductionmentioning
confidence: 99%
“…Finally, two graph theoretical studies (i.e. studies modeling topological patterns of connections in complex networks using nodes and lines) which analysed resting-state fMRI data referred to resilience from the perspective of functional brain networks [8,9]. Lo et al [8] reported an abnormal shift to greater randomization of brain network topology in patients with schizophrenia and their first-degree relatives compared to healthy volunteers, suggesting a marker of genetic or shared environmental risk for disorder.…”
Section: Key Pointsmentioning
confidence: 99%
“…studies modeling topological patterns of connections in complex networks using nodes and lines) which analysed resting-state fMRI data referred to resilience from the perspective of functional brain networks [8,9]. Lo et al [8] reported an abnormal shift to greater randomization of brain network topology in patients with schizophrenia and their first-degree relatives compared to healthy volunteers, suggesting a marker of genetic or shared environmental risk for disorder. These findings were associated with greater resilience to targeted attacks in silico, which was assessed as the simulated global efficiency of the remaining network after removing higher-degree nodes, implying a survival advantage of the integrity of brain networks with respect to real-life gray matter volume deficits [8].…”
Section: Key Pointsmentioning
confidence: 99%
“…Furthermore, graph theory has provided abundant information on the brain's functional organization in both normal and abnormal states (Park and Friston, 2013;Fornito et al, 2016). Accumulative evidence of graph analysis on human rs-fMRI research points to its potential to identify endophenotypes of brain disorders (Bullmore and Sporns, 2009a;Wang et al, 2010b;Lo et al, 2015).…”
Section: Introductionmentioning
confidence: 99%